Survival benefits of different immunotherapies for hepatocellular carcinoma: a meta-analysis highlighting age, gender, etiology, and tumor burden - Guan, Ming-Cheng; Li, Na; Ding, Qian; Sun, Di; Li, Hao; Yang, Mei; Hong, Lei; Zhu, Hong (Frontiers in Immunology, 2025)
BackgroundThe heterogeneous efficacy of immunotherapy in hepatocellular carcinoma (HCC) remains unclear. We evaluated efficacy and safety of various immunotherapeutic regimens—including immune checkpoint inhibitor (ICI) monotherapy, dual ICIs, and ICI plus targeted therapy—for unresectable HCC, to identify patient subgroups that benefit most.MethodsRandomized clinical trial evaluating immunotherapy as first-line treatment for unresectable HCC versus tyrosine kinase inhibitors (TKIs) were systematically searched. Pooled hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), and odds ratios (ORs) for objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events (TRAEs) were calculated.ResultsTwelve trials were included. Immunotherapy significantly improved OS (HR = 0.77 [0.71-0.83]) and PFS (HR = 0.73 [0.63-0.84]) versus TKIs. ICI plus targeted therapy showed the greatest benefit, reducing mortality by 27% and progression risk by 37%. Subgroup analyses revealed patients aged ≥65 years and male patients derived substantial OS and PFS benefits, particularly from ICI plus targeted therapy, whereas younger patients (<65 years) benefited more from dual ICIs. Additional favorable subgroups included Asian patients, HBV-positive patients, those with poor performance status, macrovascular invasion and/or extrahepatic spread, and Barcelona Clinic Liver Cancer stage C. Notably, female patients showed no significant OS improvement across any regimen. Moreover, non-Asian patients, those with hepatitis C, BCLC stage B, or AFP <400 ng/mL derived limited immunotherapy benefit across regimens.ConclusionsImmunotherapy improves survival in unresectable HCC, with differential subgroup benefits highlighting the necessity for personalized strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42025635108.